Investigation of the effects on the print location during selective laser melting process - Chua, Gregory Kok Hong (2018)
Selective laser melting (SLM) is an additive manufacturing process that is capable of fabricating metallic parts with a relative density up to 99%. In many experiments, the print location across the substrate is commonly overlooked and assumed to have little effect on the overall mechanical properties. An investigation of the effect of print location across the substrate based on tensile strength of the samples fabricated using SLM process is carried out. A sample of three were printed at four different location across the platform. All the samples achieved at least 489 MPa for tensile test regardless of the amount of porosities exhibit in the sample. Although results showed that different print locations across the substrate exhibit less than 1% of porosities, the samples on the right quadrants exhibit 50% more porosities as compared to the left quadrant which is validated using micro CT.